Optimal Selection of Earthquake Resisting Schemes for Jakarta-Bandung High-Speed Railway - Wei Quan; Lin Deng; Xuzheng Liu; Bibo Gao (Advances in Civil Engineering)
The Jakarta-Bandung high-speed railway is the first overseas project involving China’s high-speed railway. Owing to the high seismic intensity in this area, the optimal selection of earthquake resisting schemes is critical for short-span bridges, and such schemes are related to the safety and cost-effectiveness of the entire line. This study compares the safety and cost-effectiveness of four earthquake resisting schemes: (i) prestressed concrete (PC) simply-supported box beams using common spherical steel bearings; (ii) PC simply-supported box beams using seismic isolation bearings; (iii) steel-concrete (SC) composite simply-supported beams using seismic isolation bearings; (iv) reinforced concrete (RC) rigid frames. The results indicate that PC beams using more expensive seismic isolation bearings reduce the cost of the substructure, making it more cost-effective. In contrast, the scheme of SC composite beams is the most expensive one, and the associated maintenance costs are also the highest. Although the scheme of RC rigid frames is the cheapest among the evaluated schemes, it is only suitable for relatively stiff sites with low pier heights. Overall, PC beams with isolation bearings exhibit good seismic performance and are suitable for prefabricated construction; therefore, this scheme can be applied in various soil conditions with relatively low costs, and it is recommended for use throughout the entire Jakarta-Bandung high-speed railway.